Pengembangan Pendederan Ikan Kerapu melalui Peningkatan Kapasitas Kelompok untuk Penguatan Komoditas Unggulan Kabupaten Administratif Kepulauan Seribu, Jakarta - Irzal Effendi; Iis Diatin; Tatag Budiardi; Yani Haderoseyani (Institut Pertanian Bogor, 2021)
Nursery needs to be developed to strengthen the grouper as a superior commodity for the Seribu Islands Administrative District, Jakarta. This effort is carried out through the development of human resources (HR) and appropriate technology (AT), and hoped that the grouper nursery will become a new business unit in this district, where most of the area is sea. This activity aims to develop HR and AT for grouper nursery through training, piloting, and mentoring. This activity was carried out to 23 community members who are members of the three fish farmer groups. The training materials including the technical and management aspects of the grouper nursery. The piloting and mentoring of grouper nursery were carried out in parallel with the development of AT in the form of the application of garlic-meniran flour, and were carried out at the Sea Farming Center of PKSPL-IPB, Seribu Islands. The piloting includes preparing of cages, stocking of seeds, feeding, water quality and fish health management, sampling, harvesting, and post-harvest handling. The mentoring is carried out by serving participant visits to the center, interviews and meetings. After the training there was an increase in knowledge and skills of the participants, as well as the emergence of motivation to start a grouper nursery business. During the piloting and mentoring, the involvement and enthusiasm of the participants was relatively high and various aspects were discussed. The application of meniran-garlic flour in feeding on grouper nurseries can improve the feed conversion ratio, so that feed costs are more efficient. One of the participants has tried to run humpback grouper fish farming independently, and made a profit after two months of rearing.